Combined ROS Responsive Polydopamine-Coated Berberine Nanoparticles Effective Against Ulcerative Colitis in Mouse Model - Chang C; Liu H; Li X; Song D; Liu Y; Lu C; Zhen Y; Chen Y; Xu J; Li W; Jia X; Chen Z; et al. (International Journal of Nanomedicine, 2024)
Chenqi Chang,1 Heng Liu,2 Xiaotong Li,2 Dandan Song,1 Yue Liu,1 Chang Lu,1 Yu Zhen,1 Ying Chen,1 Jinguo Xu,1 Weidong Li,1 Xiaobin Jia,3 Zhipeng Chen,1 Rui Chen1 1School of Pharmacy, Nanjing University of Chinese Medicine, Nanjing, 210023, People’s Republic of China; 2Yunnan Provincial Key Laboratory of Entomological Biopharmaceutical R&D, College of Pharmacy, Dali University, Dali, 671003, People’s Republic of China; 3School of Traditional Chinese Pharmacy, China Pharmaceutical University, Nanjing, 211198, People’s Republic of ChinaCorrespondence: Rui Chen; Zhipeng Chen, Email chenrui@njucm.edu.cn; czpcpu2000@hotmail.comIntroduction: Enhancing the efficacy of berberine (BBR) in the treatment of ulcerative colitis (UC) through the development of dopamine-coated berberine nanoparticles (PDA@BBR NPs) with ROS-responsive and adhesive properties.Methods: Berberine nanoparticles (BBR NPs) were synthesized using the nonsolvent precipitation method, and their surfaces were coated with polydopamine (PDA) through oxidative polymerization. The PDA@BBR NPs were characterized by transmission electron microscopy (TEM), size analysis, and zeta potential analysis. Drug loading and encapsulation efficiency were analyzed using fluorescence spectroscopy. The responsiveness of these nanoparticles to reactive oxygen species (ROS) was assessed in vitro, while their adhesive properties and therapeutic efficacy on UC were evaluated in vivo.Results: Physicochemical property studies showed that PDA coated BBR NPs nanoparticles have good dispersion and stability. In vitro results showed that PDA@BBR NPs could prolong the retention time of the drug at the colonic site and could realize the gradual drug release under ROS environment. In addition, animal studies showed that PDA@BBR NPs exhibited significant anti-inflammatory effects on DSS-induced colitis and effectively reduced intestinal mucosal damage.Conclusion: PDA@BBR NPs are ROS-responsive nanoparticles that adhere well and have a high drug loading capacity. They have shown therapeutic effects in mice with UC, indicating that this formulation may be a promising treatment option. Keywords: berberine, polydopamine, ROS-responsive, adhesion retention, ulcerative colitis